Embodied social cognition investigated with virtual agents: The infinite loop between social brain and virtual reality - Oker, A. (Frontiers in Virtual Reality, 2022)
While the debate regarding the embodied nature of human cognition is still a research interest in cognitive science and epistemology, recent findings in neuroscience suggest that cognitive processes involved in social interaction are based on the simulation of others’ cognitive states and ours as well. However, until recently most research in social cognition continues to study mental processes in social interaction deliberately isolated from each other following 19th century’s scientific reductionism. Lately, it has been proposed that social cognition, being emerged in interactive situations, cannot be fully understood with experimental paradigms and stimuli which put the subjects in a passive stance towards social stimuli. Moreover, social neuroscience seems to concur with the idea that a simulation process of possible outcomes of social interaction occurs before the action can take place. In this “perspective” article, we propose that in the light of past and current research in social neuroscience regarding the implications of mirror neuron system and empathy altogether, these findings can be interpreted as a framework for embodied social cognition. We also propose that ifthe simulation process for the mentalization network works in ubiquity with the mirror neuron system, human experimentations for facial recognition and empathy need a new kind of stimuli. After a presentation of embodied social cognition, we will discuss the future of methodological prerequisites of social cognition studies in this area. On the matter, we will argue that the affective and reactive virtual agents are at the center in conducting such research.